Evaluation of compressibility and small strain stiffness characteristics of sand reinforced with discrete synthetic fibers. Issue 4 (August 2017) - Choo, H.; Yoon, B.; Lee, W.; Lee, C.
Abstract: This experimental investigation evaluates the compressibility and small strain stiffness of sand reinforced with discrete synthetic fibers. Varying fiber contents (FC), fiber aspect ratios (AR), and void ratios were selected as testing variables in this study, and the modified oedometer tests were conducted to measure the compression index ( C c ) and maximum shear modulus ( G max ) of fiber-reinforced sand. The results of this study demonstrate that the C c of the tested fiber-reinforced sand increases with an increase in FC because the packing of sand grains in the fiber-reinforced sand is very loose due to a disruption of direct contact between the sand grains due to the presence of long discrete fibers. Additionally, this disruption of direct contact between sand grains due to the fibers results in a reduction of interparticle contact and coordination number between sand grains. Therefore, the G max of tested fiber-reinforced sand decreases with an increase in FC. Most notably, the G max of the tested fiber-reinforced sand with varying FC and AR can be expressed as a single function of the void ratio at a given applied stress, which implies that the inclusion of fibers just alters the packing state of sand grains, and the interparticle contact stiffness is mainly determined by the contacts between sand grains.